The problem of the Interent addcition among physiotherapy students - Krajewska-Kułak , Elżbieta; Kropiwnicka , Ewa; Kowalczuk , Krystyna; Lankau , Agnieszka; Rozwadowska , Emilia; Lewko , Jolanta; Łukaszuk , Cecylia; Van Damme-Ostapowicz , Katarzyna; Wieczorek , Bogdan; Kułak , Wojciech; Iwański , Tomasz (Nursing in the 21st Century, 2011)
Introduction: In the contemporary world there are different forms of addiction. There are mental  (psychological) , physical (physiological) and social additions.Aim. The objective of this study was the assessment risk of the Internet addiction among physiotherapy students of the Faculty of Health Prevention of the Medical University of Białystok.Material and methods: The present study included 214 students of physiotehrapy. In this study, a questionnaire was used conisting of the personal data and four parts: part A – on-line addiction test, part B – Kimberly Young test, part C – test of intensity of the abstinence syndrome according to DSM-IV, and part D – test of intensity of “on-line addiction” assessing the events of the last year according to the diagnostic criteria of addiction ICD-10.Results: Students were using the computer 0.5 – 8 hours each day. Most often (92; 42.99%) respondents were using the Internet 2 – 3 hours daily.The Internet addiction was confirmed by 42 (19.6%) of physiotherapy students in part A survey, and rsik for Internet addition by 26 (12.1%) students. The Kimberly Young test confirmed the Internet addiction in 14 (6.5%) students and the risk for Internet addiction in 4 (1.9%) students.. The abstinence syndrome was confirmed in 14 (6.5%) students. Only 16 (7.5%) of students developed symptoms of “on-line ” addiction evaluated on the basis of ICD-10 diagnostic criteria..Conclusions: We found that 20% of physiotherapy students were using the computer more than 5 hours each day. Almost 20% of the students were classified as Internet addicts, 6%. of the students had the abstinence syndrome according to DSM-IV. Nearly 7.5% of the students had symptoms of “on-line”addiction according to the ICD-10 diagnostic criteria.